2018
DOI: 10.1007/s00127-018-1570-6
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive epidemiology of suicide attempts and suicide in the remote villages of French Guiana

Abstract: The suicide rate in remote areas in French Guiana was eight times higher than in France. The suicide of young people in remote areas in French Guiana and specifically in Amerindian villages must be better understood and prevented with contextualized and adapted care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
(19 reference statements)
0
5
0
2
Order By: Relevance
“…The most frequently used methods are hanging (72%) and AP (18%). Also, voluntary AP accounted for 50% of hospital stays for suicide attempts recorded between 2015 and 2017 in French Guiana [ 64 ]. Women account for two-thirds of suicide attempts, with a 3.7 times higher incidence of AP than men.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most frequently used methods are hanging (72%) and AP (18%). Also, voluntary AP accounted for 50% of hospital stays for suicide attempts recorded between 2015 and 2017 in French Guiana [ 64 ]. Women account for two-thirds of suicide attempts, with a 3.7 times higher incidence of AP than men.…”
Section: Discussionmentioning
confidence: 99%
“…Women account for two-thirds of suicide attempts, with a 3.7 times higher incidence of AP than men. In the Maripasoula municipality, the rate of suicide attempts by paraquat absorption was the highest, at 46% [ 64 ]. Albano et al [ 8 ], in a systematic review of toxicological findings of self-poisoning suicidal deaths, found that the most involved substances in low- and middle-income countries with significant agricultural areas were pesticides such as organophosphates and carbamates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women in French Guiana are substantially more affected by overweight/obesity and type 2 diabetes [ 18 ]. Although women consume more health services, they remain more affected by these major risk factors [ 21 , 22 ], and when exposed, they are more prone to cardiovascular risks than men [ 23 ]. The proportion of obese (body mass index > 30 kg/m 2 ) was greater among French Guianese women (23%) than in women in mainland France (12%) and French Guianese men (13% versus 12% in mainland France) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…68 ). Le taux de suicide parmi ces jeunes serait entre 8 et 20 fois plus élevé que celui relevé en Guyane et dans l'Hexagone [ 15 , 154 , 275 ]. Les peuples amérindiens côtiers (Kaliña, Palikur et Arawak) sont également concernés, mais à moindre échelle.…”
Section: Phénomènes Spécifiques à La Guyaneunclassified